Teori Kausalitas dalam Membangun Kontruksi Kasus Pembunuhan Vina Cirebon - Hamirul (PT PUSTAKA CENDEKIA GROUP, 2024)
The case of Vina and Eky in Cirebon that occurred in 2016 still leaves a portrait of law enforcement that is disproportionate and unprofessional and takes action, this is seen from the complexity of this problem, researchers want to know the application of the theory of causality in building the construction of murder in 2016 and applied to the facts and evidence found in 2024 now. In this study, we will apply a comprehensive qualitative approach to be able to explore and understand various aspects related to the Vina murder case in depth. This case study method will be our main approach, because through case studies we can conduct an in-depth and holistic investigation of this specific phenomenon, including the legal process that occurred, the response of the community, and its implications for the enforcement of justice in Indonesia. From the results of the study, it was found that the construction built on the murder case of Vina and Eky in Cirebon when viewed from the theory of causality, it was found that this case was not murder and rape but a single accident.